Amino-functionalized mesoporous silica based polyethersulfone-polyvinylpyrrolidone composite membranes for elevated temperature proton exchange membrane fuel cells - Zhang, Jin; Lu, S.; Zhu, H.; Chen, Kongfa; Xiang, Y.; Liu, Jian; Forsyth, M.; Jiang, San Ping (Royal Society of Chemistry, 2016)
It is important to find alternative membranes to the state-of-the-art polybenzimidazole based high temperature proton exchange membranes with high proton conductivity at elevated temperature but with simple synthesis procedures. In this work, inorganic-organic nanostructured hybrid membranes are developed based on a polyethersulfone-polyvinylpyrrolidone (PES-PVP) polymeric matrix with hollow mesoporous silica (HMS), amino-functionalized hollow mesoporous silica (NH2-HMS) and amino-functionalized mesoporous silica (NH2-meso-silica). The composite membranes show a significant increase in proton conductivity and a decrease in the activation energy for proton diffusion in comparison with the phosphoric acid (H3PO4, PA) doped PES-PVP membrane. And the composite membrane with NH2-HMS shows the best performance under the conditions in this study, achieving the highest proton conductivity of 1.52 × 10-1 S cm-1 and highest peak power density of 480 mW cm-2 at 180 °C under anhydrous conditions, which is 92.7% higher than that of the PA doped PES-PVP membrane at identical conditions. Such enhancement results from the facilitated proton transportation in the ordered mesoporous channels via the hydrogen bond between the -NH2 groups and H3PO4. The high water retention capability of silica materials with a hollow structure also contributes to the decrease of the activation of proton diffusion. Consequently, the results show promising potential of the NH2-HMS based PES-PVP composite membrane for the elevated temperature proton exchange membrane fuel cells.